LOCAL AREA NETWORK (LAN) UTILIZATION IN IMPROVING CREDIT SERVICE (Case Study At PT. Bank Rakyat Indonesia Cabang Kawi, Malang) - Mustika Agusti Saffira (Fakultas Ilmu Administrasi Universitas Brawijaya, 2013)
This study was conducted based on the lack of computer utilization in a public and private organizations, but thanks to the IT expert’s innovation, it creates a computer network called LAN (Local Area Network). LAN greatly assists in the distribution of information among divisions quickly and effectively. Along with developments in telecommunications, networking technology is now venturing into the field of banking, computer networks has become one of the supporting factors in terms of community service is a data processing on the credit division and assisted by a LAN that can accelerate the performance in the company. Similarly, in Bank Rakyat Indonesia Kawi Branch, Malang using LAN expected data processing of credit service users to be optimal and able to produce accurate information and be available easily. However, in Bank Rakyat Indonesia Kawi Branch, Malang there are shortcomings in LAN utilization that is lack of system components, systems environmental, systems processing and systems target resulting in inhibition of employee performance. Based on the survey results revealed that the LAN is used at Bank Rakyat Indonesia Kawi Branch, Malang in credit service is not maximized. Topology used is the bus topology can be replaced with a star topology because the star topology has more advantages. Uses of software and hardware that consumes less support in improving employee performance and therefore in this study the authors also provide advice to software and hardware needed to support the increase in the credit services. Internet use at Bank Rakyat Indonesia Kawi Branch, Malang is less than the maximum should implement an intranet to help information systems to be more easily, smoothly and efficiently. Keywords: Local Area Network (LAN), Credit Service